2018
DOI: 10.4148/0146-9282.1692
|View full text |Cite
|
Sign up to set email alerts
|

Instructors’ Perceptions and Experiences Re: Creating and Implementing Customized E-Texts in Education Courses

Abstract: Hereinafter referred to within this article as the "COE." 2 Hereinafter referred to within this article as the "initiative." 3 The term "instructor" as used within this article refers to all individuals who received funding under the initiative, irrespective of faculty rank.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…As suggested previously, one of the most commonly recurring challenges was the amount of time and effort that implementation required for participating faculty, and some program organizers observed a need for increased recognition of faculty efforts in this area with regard to tenure and other professional advancement decisions (Agee & Mune, 2014;Delimont et al, 2016;Bazeley et al, 2019). The need for relevant faculty training and support was also widely recognized, and faculty feedback at some institutions indicated that more support was needed than had been provided (Bailey & Poo, 2018;Young, 2016;Delimont et al, 2016;Subramony, 2018).…”
Section: Identified Challengesmentioning
confidence: 99%
“…As suggested previously, one of the most commonly recurring challenges was the amount of time and effort that implementation required for participating faculty, and some program organizers observed a need for increased recognition of faculty efforts in this area with regard to tenure and other professional advancement decisions (Agee & Mune, 2014;Delimont et al, 2016;Bazeley et al, 2019). The need for relevant faculty training and support was also widely recognized, and faculty feedback at some institutions indicated that more support was needed than had been provided (Bailey & Poo, 2018;Young, 2016;Delimont et al, 2016;Subramony, 2018).…”
Section: Identified Challengesmentioning
confidence: 99%